Upaya Pemerintah dalam Mengatasi Pelanggaran Hak dan Pengingkaran Kewajiban Warga Negara Berdasarkan UUD 1945 (Indo-MathEdu Intellectuals Journal, 2024)
The purpose of this study is to find out what factors cause the violation of rights and denial of citizens' obligations, to find out cases of violations of rights and denials of citizens' obligations and how the role of the government in overcoming violations of rights and denials of citizens' obligations. This research uses a qualitative approach with a library research method. The main source of this research is the research article published through the google scholar website. Data analysis was carried out qualitatively consisting of data reduction, data presentation, and conclusion drawn. The results of the analysis show that rights and obligations are interrelated, so that in their implementation they must be carried out in a balanced manner. Violations of citizens' rights occur when citizens are unable to exercise or obtain their rights as determined by law. The imbalance between the implementation of citizens' rights and responsibilities causes violations of rights and denials of citizens' responsibilities. The causes of violations of rights and denial of citizens' obligations are caused by the administration of the state and society